Orientation and Mobility Skills of Children with Visual Impairment in Low-income Families in Central Uganda - Niyisabwa, Odette Tumwesigye; Musenyente, Elijah (INKLUSI, 2021)
The study investigated the Orientation and Mobility (O&M) skills of children with visual impairment in low-income families in Central Uganda. Specifically, the study explored the existing situation of Orientation and Mobility (O&M) skills of children with visual impairment, their independence, as well as factors responsible for the existing situation. The qualitative research collected information from parents or guardians of children with visual impairment and a Social Worker. The findings indicated that children with visual impairment had poor O&M skills because of lack of involvement in activities. These due to several reasons that included overprotection, no exposure to stimulating environments, and negative attitudes which consequently led to neglect, mistreatment, starvation, and fear to initiate movement. Results also indicated that, involvement in rehabilitation care for the children was generally lacking among fathers than mothers. Artikel ini meneliti keterampilan Orientasi dan Mobilitas (O&M) anak-anak tunanetra di keluarga berpenghasilan rendah di Uganda Tengah. Secara khusus, penelitian ini mengeksplorasi kondisi tingkat keterampilan Orientasi dan Mobilitas (O&M) anak tunanetra, kemandirian mereka, serta faktor-faktor yang mempengaruhi atas kondisi yang ada. Penelitian kualitatif dalam artikel ini mengumpulkan informasi dari para orang tua atau wali anak tunanetra dan seorang pekerja sosial yang dipilih secara sengaja. Temuan menunjukkan bahwa anak tunanetra memiliki keterampilan O&M yang buruk karena kurangnya keterlibatan dalam kegiatan. Di antara penyebabnya adalah perlindungan orang tua yang berlebihan, tidak memiliki lingkungan yang stimulatif, dan sikap negatif yang mengakibatkan pengabaian, perlakuan buruk, kelaparan, dan ketakutan untuk memulai gerakan. Hasil juga menunjukkan bahwa, keterlibatan bapak dalam perawatan rehabilitasi untuk anak-anak umumnya lebih sedikit daripada keterlibatan ibu.